PROJECT WORK NATURAL EXTENSION STUDY OF CONTENT-BASED TEACHING - Rustamov, Ilxom; Ataboyev Isroiljon Mirza o`g`li (Журнал иностранных языков и лингвистики, 2023)
Projects involving hobbies, crafts, physical activity, sports and community service are extremely fruitful for English conversation groups, provided only English is spoken during a particular activity. All you need to do is find common ground between your group’s interests and your supervision skills, and allocate enough time, space, and equipment to create projects that are successful in themselves and in practice